Investigating relationship between cognitive styles, personality traits, and academic achievement of adolescents (Journal of Advances and Scholarly Researches in Allied Education, 2024)
This study explores the intricate relationships between cognitive styles, personality traits, and academic achievement among adolescents. Cognitive styles refer to the preferred ways individuals process information, while personality traits are enduring characteristics that influence behavior and attitudes. The research involved a diverse sample of adolescents, utilizing a combination of cognitive style inventories, personality assessments, and academic performance records. The findings revealed significant correlations between specific cognitive styles and academic success, with certain personality traits acting as mediators in this relationship. The study underscores the importance of considering both cognitive and personality factors in educational strategies to enhance student performance. The implications for educators and policymakers are discussed, emphasizing tailored interventions that align with students' cognitive and personality profiles.